High-efficiency recycling method for Mo and Ni from spent catalyst via soda roasting and solvent extraction. (20th September 2022) - Gao, Bingying; Jiang, Haohao; Zeng, Man; Peng, Mingguo; Hu, Linchao; Zhang, Wenyi; Mao, Linqiang
Abstract: The catalyst Mo–Ni/Al2 O3 is commonly used in the hydrodesulfurization of petroleum fractions. The catalyst is discarded when its catalytic activity does not meet the requirement of the process, and the spent catalyst is usually classified as hazardous waste due to its significant heavy-metal content. The spent catalyst usually has a high commercial recovery value as a secondary resource for high-value metals, but the simple and high efficiency recovery method is still lacking. A high-efficiency recovery method for Mo and Ni from spent Mo–Ni/Al2 O3 catalyst via soda roasting and solvent extraction was developed in this study. MoO3 interacts with Al2 O3 and forms a new phase, Al2 (MoO4 )3, during blank roasting at 600–700 °C. Al2 (MoO4 )3 further transforms into NaMoO4 during soda roasting at 950 °C, and over 99.1% of Mo can be leached using hot water (60 °C). Solvent extraction with the trioctyl tertiary amine (N235) is employed to separate Mo from the leaching solution, and approximately 99.45% of Mo can be enriched through single-stage extraction. Around 99.2% of Mo can be stripped from loaded N235 using 8 M NH3 H2 O. Further, PO4 3− and SiO3 2− can be removed from the stripping solution using Mg(NO3 )2, and Mo is recycled in the form of MoO3, i.e., a product of the ammonium precipitation and calcining process. Over 99.3% of Ni can be leached from the solid residue using 30% volume fraction of H2 SO4 and the solvent extraction can be enriched using diiso-octylphosphate (DP). Ni is finally recycled from the stripping solution as NiSO4 2H2 O via evaporative crystallization. The total Mo and Ni recovery efficiencies of the newly developed integrated approach are 97.8% and 98.1%, respectively. Al is also recycled in the form of α-Al2 O3 via chemical precipitation and calcination. The proposed approach is simple, with a high recovery rate and high selectivity, and can be applied to the recycling and disposal of spent Mo–Ni/Al2 O3 catalyst. Highlights: A new recovery way for Mo and Ni from spent catalyst was developed. MoO3 interacts with Al2 O3 and forms a new phase of Al2 (MoO4 )3 . P and Si can be removed from stripping solution by Mg salts. The total recovery efficiency of Mo and Ni can be obtained at 97.8% and 98.1%.